1996
DOI: 10.7883/yoken1952.49.15
|View full text |Cite
|
Sign up to set email alerts
|

Effective Isolation of Mpb64 From a Large Volume of Culture Filtrate of Mycobacterium Bovis BCG Tokyo

Abstract: SUMMARY:MPB64, a secretory protein of Mycobacterium bovis BCG Tokyo , was isolated from a culture filtrate of the bacteria in Sauton synthetic medium harvested on day 8. The protein was isolated by five steps; (i) concentration of the culture filtrate by cutting the molecules smaller than 5 kDa with the Millipore Pellicon Cassette system, (ii) affinity separation by a Phenyl Sepharose CL-4B column, (iii) separation with a DEAE-Sepharose CL-6B column with 3 M urea, (iv) separation with a Sephacryl S200HR column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…MPB-59 (30 kDa) was prepared from culture filtrates of M. bovis BCG Tokyo 172 as described previously (19). The bacteria were cultured in Sauton synthetic medium at 37°C without aeration for 8 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPB-59 (30 kDa) was prepared from culture filtrates of M. bovis BCG Tokyo 172 as described previously (19). The bacteria were cultured in Sauton synthetic medium at 37°C without aeration for 8 days.…”
Section: Methodsmentioning
confidence: 99%
“…with a molecular weight 5,000 cutoff membrane (YM-3; Amicon, Beverly, Mass.). Proteins were further concentrated with 60% saturated ammonium sulfate and fractionated high-pressure liquid chromatography (i) affinity chromatography with phenyl Sepharose CL-4B, (ii) DEAE Sepharose CL-6B ion exchange, (iii) Sephacryl S200 HR gel filtration, and (iv) re-ion-exchange with DEAE Sepharose CL-6B (all from Pharmacia LKB, Uppsala, Sweden) (19). Following sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis with 10 g of purified MPB-59 protein, a single 30-kDa band was stained by silver (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analysis of various TB proteins has confirmed that MPB64 is identical to MPT64, a protein produced by M. tuberculosis . Non‐tuberculous mycobacteria do not produce MPB64; it is specifically secreted by M. tuberculosis complex (17–21). MPB64 was first isolated by Harboe and Nagai in 1986, whereas Li and colleagues identified it as a secreted protein specific to tuberculous mycobacteria in 1993 (7, 3).…”
Section: Discussionmentioning
confidence: 99%
“…The protein was isolated from a culture ltrate of M. bovis BCG Tokyo, an 8-d culture, and puri ed according to published techniques (5). The purity of the protein was con rmed by silver staining.…”
Section: Mpb -64 Proteinmentioning
confidence: 99%